Clinical Profile of Patients with Hypertensive Emergency Referred to a Tertiary Hospital in the Western Cape Province of South Africa - Talle, Mohammed A.; Doubell, Anton F.; Robbertse, Pieter-Paul S.; Lahri, Sa'ad; Herbst, Philip G. (Current Hypertension Reviews, 2023)
Background: Despite advances in managing hypertension, hypertensive emergencies remain a common indication for emergency room visits. Our study aimed to determine the clinical profile of patients referred with hypertensive emergencies.Methods: We conducted an observational study involving patients aged ≥18 years referred with hypertensive crisis. A diagnosis of hypertensive emergencies was based on a systolic blood pressure (BP) ≥180 mmHg and/or a diastolic BP ≥110 mmHg, with acute hypertension-mediated organ damage (aHMOD). Patients without evidence of aHMOD were considered hypertensive urgencies. Hypertensive disorders of pregnancy and unconscious patients were excluded from the study.Results: Eighty-two patients were included, comprising 66 (80.5%) with hypertensive emergencies and 16 (19.5%) with hypertensive urgencies. The mean age of patients with hypertensive emergencies was 47.9 (13.2) years, and 66.7% were males. Age, systolic BP, and duration of hypertension were similar in the hypertensive crisis cohort. Most patients with hypertensive emergencies reported nonadherence to medication (78%) or presented de novo without a prior diagnosis of hypertension (36%). Cardiac aHMOD (acute pulmonary edema and myocardial infarction) occurred in 66%, while neurological emergencies (intracranial hemorrhage, ischemic stroke, and hypertensive encephalopathy) occurred in 33.3%. Lactate dehydrogenase (LDH) (P < 0.001), NT-proBNP (P=0.024), and cardiac troponin (P<0.001) were higher in hypertensive emergencies compared to urgencies. LDH did not differ in the subtypes of hypertensive emergencies.Conclusion: Cardiovascular and neurological emergencies are the most common hypertensive emergencies. Most patients reported nonadherence to medication or presented de novo without a prior diagnosis of hypertension.
Keywords: lactate dehydrogenase